Estudio de factibilidad para la creación de un restaurante temático del plátano en Armenia - Quindío (2013)
The idea is mainly based on the elaboration of an investment project for a banana thematic restaurant located on the road between Armenia and La Tebaida, a kilometer before the Murillo inspection in which there is a place known as Titina; below this, there is a small peasant House which would be the place where the thematic restaurant of the banana would work . The necessity of creating the restaurant comes from the familiarity that colleague Angela María Valencia has with products to be sold since its proximity to "Los Arrieros" restaurant provides the information needed to carry it out. The restaurant has great strengths as being unique in the region because it is a thematic restaurant where the customer feels emotions and intrigues caused by knowledge and service quality, it has strict control over the proceedings, both administrative processes as in the production process. Assessing the reality of the hospitality industry in Armenia, we have that there is a low roots of food culture and knowledge on bananas, low specializing in Creole food scarce, and low general knowledge of typical food products of our coffee culture. for these reasons we developed a feasibility study for the creation of a banana thematic restaurant where we can stipulate the current market situation, also we determined the technical and engineering needs, were required organizational and legal models, assessing the environmental aspects was determined the economic and financial feasibility of itself. the products to be sold are four main dishes, sancocho, bandeja paisa, sobrebarriga, patacón con todo, also have drinks such as porridge, syrup, sugar water with lemon, among others. Besides having a very friendly environment with a great design and décor related with banana the restaurant provides customers different knowledge of it with the help of employees, are making music samples and artwork during the customer stay; inside the restaurant It also has a small shop for the sale of snacks, fresh banana, souvenirs, books, magazines and more. With this feasibility study was determined that it is a viable idea because it has a large enough demand for the development of itself, bringing revenue to the region's economic growth by generating employment and increasing sources of knowledge not only about coffee but also traditional products like bananas that make our region unique on culinary varieties.